(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Background: Nasogastric tube (NGT) is an important means of delivering food and medicine to patients who are unable to meet their daily needs. It is used to care for patients around the world who suffer from many diseases, such as falling into a coma or having an increased frequency of breathing, as well as those who are placed on a ventilator. Premature babies, as well as children who suffer from weight loss and dehydration, and in other pathological conditions that require its use for the purpose of giving food and medicine However, in addition to its positive aspects, there are many problems related to it, such as its entry into the respiratory system and other problems that lead to death. Therefore, the correct position of the feeding tube must be ensured in several ways before giving food to the child. Purpose: The aim of the study is to determine the efficiency of the auscultation method in determining the position of the feeding tube. Methods: The study was carried out from September 15, 2023 to April 15, 2024. Fifty children under the age of five who were admitted to the Babel Maternity and Children’s Teaching Hospital were included. A quantitative descriptive design was used in this study. Results: auscultation method indicating that the feeding tube was ‎inside the stomach, meaning that 96% were inside the stomach. The agreement between the auscultation method and X-rays was very weak. Conclusion: The auscultation method is inaccurate in determining the position of the feeding tube in children and the results of the auscultation method are also affected by many external environmental factors, as well as the patient’s condition and the skill of the nurses.